2012
DOI: 10.1063/1.4756789
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and performance optimization of the magneto-optical (Tb1−xRx)3Al5O12 (R = Y, Ce) transparent ceramics

Abstract: Ferroelectric domain morphology and structure in Li-doped (K,Na)NbO3 ceramics J. Appl. Phys. 112, 052005 (2012) Room temperature ferroelectric and magnetic investigations and detailed phase analysis of Aurivillius phase Bi5Ti3Fe0.7Co0.3O15 thin films J. Appl. Phys. 112, 052010 (2012) Electric field induced phase instability in typical (Na,K)(Nb,Sb)O3-LiTaO3 ceramics near orthorhombic and tetragonal phase boundary Appl. Phys. Lett. 101, 092906 (2012) Effects of Gd substitution on microstructures and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The newly developed FR based on TGG ceramics should accelerate the development of high-pulse-energy lasers, high-power lasers, and their applications. Our findings, which underline the advantages of magneto-optical transparent ceramics, should also promote the study of other types of magneto-optical transparent ceramics, such as terbium aluminum garnet ceramics [24,25].…”
mentioning
confidence: 71%
“…The newly developed FR based on TGG ceramics should accelerate the development of high-pulse-energy lasers, high-power lasers, and their applications. Our findings, which underline the advantages of magneto-optical transparent ceramics, should also promote the study of other types of magneto-optical transparent ceramics, such as terbium aluminum garnet ceramics [24,25].…”
mentioning
confidence: 71%
“…Here, due to the electronic transition of 4f 8 → 4f 7 5d89, the Tb 3+ ion offers one of the highest paramagnetic susceptibilities ( J = 6, g = 1.46) and magnetic moments (9.5–9.72 μ eff ) of all rare earth ions. Consequently, the most promising bulk MO material is terbium aluminum garnet (Tb 3 Al 5 O 13 , TAG, V B ~ 180 rad/T/m)1011, which is not yet available commercially, though. Instead, terbium gallium garnet single crystals (Tb 3 Ga 5 O 13 , TGG, V B ~ 134 rad/T/m)12 are presently the most widely used commercial MO materials.…”
mentioning
confidence: 99%
“…Some researchers have found that the quantum based super-exchange interaction between Tb 3 þ and other paramagnetic Re 3 þ ions can occur, greatly enhancing the Faraday effect. Ce 3 þ doped TAG ceramic has a V of 199.55 rad T À 1 m À 1 at 632.8 nm, 16% larger than that of TAG [14]. {Tb 3 }[Sc 1.95 Lu 0.05 ](Al 3 ) O 12 (TSLAG) single crystal having an increment of 20% of V compared to TGG dues to the doping of Sc 3 þ , Lu 3 þ , Al 3 þ ions [15,16].…”
Section: Introductionmentioning
confidence: 97%